Competing sexual-asexual generic names in Agaricomycotina (Basidiomycota) with recommendations for use - Joost A. Stalpers; Scott A. Redhead; Tom W. May; Amy Y. Rossman; Jo Anne Crouch; Marc A. Cubeta; Yu-Cheng Dai; Roland Kirschner; Gitta Jutta Langer; Karl-Henrik Larsson; Jonathan Mack; Lorelei L. Norvell; et al. (IMA Fungus)
Abstract With the change to one scientific name for fungal taxa, generic names typified by species with sexual or asexual morph types are being evaluated to determine which names represent the same genus and thus compete for use. In this paper generic names of the Agaricomycotina (Basidiomycota) were evaluated to determine synonymy based on their type. Forty-seven sets of sexually and asexually typified names were determined to be congeneric and recommendations are made for which generic name to use. In most cases the principle of priority is followed. However, 16 generic names are recommended for use that do not have priority and thus need to be protected: Aleurocystis over Matula; Armillaria over Acurtis and Rhizomorpha; Asterophora over Ugola; Botryobasidium over Acladium, Allescheriella, Alysidium, Haplotrichum, Physospora, and Sporocephalium; Coprinellus over Ozonium; Coprinopsis over Rhacophyllus; Dendrocollybia over Sclerostilbum and Tilachlidiopsis; Diacanthodes over Bornetina; Echinoporia over Echinodia; Neolentinus over Digitellus; Postia over Ptychogaster; Riopa over Sporotrichum; Scytinostroma over Artocreas, Michenera, and Stereofomes; Tulasnella over Hormomyces; Typhula over Sclerotium; and Wolfiporia over Gemmularia and Pachyma. Nine species names are proposed for protection: Botryobasidium aureum, B. conspersum, B. croceum, B. simile, Pellicularia lembosporum (syn. B. lembosporum), Phanerochaete chrysosporium, Polyporus metamorphosus (syn. Riopa metamorphosa), Polyporus mylittae (syn. Laccocephalum mylittae), and Polyporus ptychogaster (syn. Postia ptychogaster). Two families are proposed for protection: Psathyrellaceae and Typhulaceae. Three new species names and 30 new combinations are established, and one lectotype is designated.